PENGEMBANGAN INSTRUMEN EVALUASI MEMBACA KRITIS TEKS DI KURIKULUM MERDEKA - Pitrianti, Siti; Nofrahadi, Nofrahadi; Ambasari, Nais; Satria, Dadi (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
The development of evaluation instruments for reading texts in the Independent Curriculum focuses on critical thinking skills, including analyzing, interpreting, and evaluating information from the texts read. In the Independent Curriculum, the focus of evaluation is not only at the end, but also on the learning process. Reading instruments must be oriented towards measuring students' cognitive abilities, skills, and attitudes, not just mastery of text material. This phenomenon shows a shift from a conventional evaluation approach to a more comprehensive and holistic evaluation. The purpose of this study is to develop a valid, reliable, and practical critical reading evaluation instrument in the Independent Curriculum. This study uses the R&D method, with the instruments that have been prepared being tested for validity and tested for feasibility. Based on the results of the trial, it can be concluded that the evaluation tool is feasible to be applied.